The science of education: using learning theory to solve teaching problems in medical education. - Shaughnessy, Allen F.; Erlich, Deborah R. (Education for Primary Care, 2022)
Although theories do not play a major role in clinical medicine, the application of established theories of education can improve medical teaching. By understanding and harnessing learning theories, clinician educators can solve common teaching problems, thoughtfully craft their teaching sessions, determine whether learners or residents have achieved the intended learning objectives, and even earn higher course ratings. Key theories to be aware of include cognitive load theory, social learning theory, experiential learning, constructivism, humanism, behaviourism and connectivism. Various teaching problems are presented, along with explanations rooted in educational theory and possible solutions for use in the clinical educational setting.